Omission and addition in the Vietnamese translation of Frances Hodgson Burnett’s “The secret garden” = Chiến lược dịch thêm và lược dịch trong bản dịch tiếng Việt tác phẩm « Khu vườn bí mật » của tác giả Frances Hodgson Burnett - Lê, Thị Thùy Linh (2021)
The goals of this study are to identify and investigate the application of omission and addition strategies in the Vietnamese translation of The Secret Garden by Nguyen Tuan Khanh as well as to examine the perspectives held by chosen readers and the translator toward these applications. The idea is to reinforce the roles of addition and omission during the translation process as two translation strategies instead of miscues. Data for this study were obtained through the help of questionnaire and interview. Firstly, the questionnaire was delivered to a number of selected readers in order to get their ideas on the issue, particularly if they are favored or infavored of addition and omission applications together with the reasons for their choice. A questionnaire was also distributed to the translator in order to discover the motives for his applications of the two strategies and compare them with the readers’ opinions. Furthermore, a semi-structured interview with the translator was conducted with the aim of getting the translator’s perspectives on the employment of addition and omission during translation process in general. On the basis of the results of this research, it can be concluded that addition strategy tends to be utilized more than omission, and most of the instances detected in the case study is favored by readers. One interesting point can be found is that the translator did make a lot of assumptions about readers when translating the novel, and these assumptions actually match with the majority of respondents’ opinions on the topic of reasons for the applications of those investigated addition and omission phenomena. Moreover, the data also support the expectation that addition and omission play a certain role when translators render messages from one language to another.